Multiplying polynomials
Multiplying polynomials with the following three good examples will help you master this topic once and for all. That is all you will need. It could be very useful though to review
the
multiplication of binomials.
Examples about multiplying polynomials
Example #1:
Multiply 4x
^{3} + 2x + 5 by 3x
^{4} + x + 6
(4x
^{3} + 2x + 5) × (3x
^{4} + x + 6)
Important concept
You must know what a term is when multiplying polynomials. It is because the goal is to multiply each term of the polynomial on the left by each term of the polynomial on the right and then adding the whole thing!
We will show the result of each multiplication or whatever will be added together in bold.
The polynomial on the left is 4x
^{3} + 2x + 5
Look at it carefully. Each term is separated by an addition sign.
So the first term is 4x
^{3}
The second term is 2x
The third term is 5
The polynomial on the right is 3x
^{4} + x + 6
Again, each term is separated by an addition sign.
So the first term is 3x
^{4}
The second term is x
The third term is 6
Now multiply the first term of the polynomial on the left that is 4x
^{3} by each term of the polynomial on the right and these are 3x
^{4},
x, and 6.
Let's do it!
4x
^{3} × 3x
^{4} = 4 × 3 × x
^{3} × x
^{4} = 12x
^{ 3 + 4} =
12x^{7}
4x
^{3} × x = 4 × x
^{3} × x = 4 × x
^{3} × x
^{1} = 4x
^{ 3 + 1} =
4x^{4}
4x
^{3} × 6 = 4 × 6x
^{3} =
24x^{3}
Next, multiply the second term of the polynomial on the left that is 2x by each term of the polynomial on the right and these are 3x
^{4},
x, and 6.
2x × 3x
^{4} = 2 × 3 × x × x
^{4} = 2 × 3 × x
^{1} × x
^{4} = 6x
^{ 1 + 4} =
6x^{5}
2x × x = 2 × x × x = 2 × x
^{1} × x
^{1} = 2x
^{ 1 + 1} =
2x^{2}
2x × 6 = 2 × 6x =
12x
Finally, multiply the third term of the polynomial on the left that is 5 by each term of the polynomial on the right and these are 3x
^{4},
x, and 6.
5 × 3x
^{4} =
15x^{4}
5 × x =
5x
5 × 6 =
30
Adding the result in bold together, we get:
12x
^{7} + 4x
^{4} + 24x
^{3} + 6x
^{5} + 2x
^{2} + 12x + 15x
^{4} + 5x + 30
Combine like terms
12x
^{7} + (4x
^{4} + 15x
^{4}) + 24x
^{3} + 6x
^{5} + 2x
^{2} + (12x + 5x) + 30
12x
^{7} + 19x
^{4} + 24x
^{3} + 6x
^{5} + 2x
^{2} + 17x + 30
Example #2:
Multiply 4x
^{3} − 2x + 5 by 3x
^{4} + x − 6
Almost the same problem. We just incorporated a couple of subtraction signs.
My teaching experience has taught me that when multiplying polynomials, it is best to say to students to replace minus with + 
Then, do the exact same thing you did in example #1
(4x
^{3} − 2x + 5) × (3x
^{4} + x − 6) = (4x
^{3} + 2x + 5) × (3x
^{4} + x + 6)
4x
^{3} × 3x
^{4} =
12x^{7}
4x
^{3} × x =
4x^{4}
4x
^{3} × 6 = 4 × 6x
^{3} =
24x^{3}
Notice this time that the second term of the polynomial on the left has a negative next to it! same thing for the third term of the polynomial on the right.
Pay careful attention to this when multiplying polynomials!
2x × 3x
^{4} = 2 × 3 × x × x
^{4} = 2 × 3 × x
^{1} × x
^{4} = 6x
^{ 1 + 4} =
6x^{5}
2x × x = 2 × x × x = 2 × x
^{1} × x
^{1} = 2x
^{ 1 + 1} =
2x^{2}
2x × 6 = 2 × 6x =
12x
5 × 3x
^{4} =
15x^{4}
5 × x =
5x
5 × 6 =
30
Adding the result in bold together, we get:
12x
^{7} + 4x
^{4} + 24x
^{3} + 6x
^{5} + 2x
^{2} + 12x + 15x
^{4} + 5x + 30
Combine like terms
12x
^{7} + (4x
^{4} + 15x
^{4}) + 24x
^{3} + 6x
^{5} + 2x
^{2} + (12x + 5x) + 30
12x
^{7} + 19x
^{4} + 24x
^{3} + 6x
^{5} + 2x
^{2} + 17x + 30
Multiplying polynomials should be a breeze if you really understand the three examples above. Take a look also at the one in the figure below.

Oct 20, 21 04:45 AM
Learn how to find the multiplicity of a zero with this easy to follow lesson
Read More
Enjoy this page? Please pay it forward. Here's how...
Would you prefer to share this page with others by linking to it?
 Click on the HTML link code below.
 Copy and paste it, adding a note of your own, into your blog, a Web page, forums, a blog comment, your Facebook account, or anywhere that someone would find this page valuable.